3‐D molecular stars with covalent axial bonding. Issue 15 (5th March 2023) - Guan, Xiao‐Ling; Sun, Rui; Jin, Bo; Yuan, Caixia; Wu, Yan‐Bo
Abstract: In designing three‐dimensional (3‐D) molecular stars, it is very difficult to enhance the molecular rigidity through forming the covalent bonds between the axial and equatorial groups because corresponding axial groups will generally break the delocalized π bond over equatorial frameworks and thus break their star‐like arrangement. In this work, exemplified by designing the 3‐D stars Be2 ©Be5 E5 + (E = Au, Cl, Br, I) with three delocalized σ bonds and delocalized π bond over the central Be2 ©Be5 moiety, we propose that the desired covalent bonding can be achieved by forming the delocalized σ bond(s) and delocalized π bond(s) simultaneously between the axial groups and equatorial framework. The covalency and rigidity of axial bonding can be demonstrated by the total Wiberg bond indices of 1.46–1.65 for axial Be atoms and ultrashort Be‐Be distances of 1.834–1.841 Å, respectively. Beneficial also from the σ and π double aromaticity, these mono‐cationic 3‐D molecular stars are dynamically viable global energy minima with well‐defined electronic structures, as reflected by wide HOMO‐LUMO gaps (4.68–5.06 eV) and low electron affinities (4.70–4.82 eV), so they are the promising targets in the gas phase generation, mass‐separation, and spectroscopic characterization. Abstract : The binary σ + π double aromatic three‐dimensional (3‐D) five‐point stars Be2 ©Be5 E5 + (E = Au, Cl, Br, I) stars were confirmed to be the dynamically stable global energy minima. They are unprecedented in that their axial Be atoms interact with the equatorial group not through the ionic bond, but through four delocalized covalent bonds, which lead to the high molecular rigidity, as reflected by the ultrashort axial Be‐Be distance of 1.834–1.841 Å.